Ground and surface water hydrology - Mays, Larry W. (Hoboken, N.J. : Wiley, 2012)
'Larry Mays' Hydrology is a comprehensive text stressing fundamentals of hydrologic process for both surface water hydrology and groundwater hydrology. The text makes use of internet resources, such as free modeling tools, to help solve more complicated and real-world problems more quickly, and motivate interest in the topics.The book focuses on Water Resources Engineering as a subset of Hydrology and Water Resources Engineering covering sources of water that are useful to humans. Hydrology includes both water resources engineering, and more in-depth coverage of the hydrologic cycle (the continuous circulation of water in the atmosphere, land, surface water, and groundwater). The hydrologic effects of climate change is covered, as well as newer topics in hydrology including use of GIS, remote sensing, NEXRAD and other topics. Emphasis is given to the hydrologic processes and practice in the different climates: humid climate, cold climate, temperate climate, and arid and semi-arid climate'--
Machine generated contents note: Chapter 1 Hydrology, Climate Change, and Sustainability.1.1 Introduction to Hydrologic Processes.1.2 Climate Change Effects and the Hydrologic Cycle.1.3 Anthropogenic Effects on the Hydrologic Cycle.1.4 Water Resources Sustainability.1.5 Hydrologic Budgets.1.6 Hydrologic Data and Publication Sources.1.7 U.S. Geological Survey Publications.Problems.References.Chapter 2 Occurrence of Groundwater.2.1 Origin of Groundwater.2.2 Rock Properties Affecting Groundwater.2.3 Vertical Distribution of Groundwater.2.4 Zone of Aeration.2.5 Zone of Saturation.2.6 Geologic Formations as Aquifers.2.7 Types of Aquifers.2.8 Storage Coefficient.2.9 Groundwater Basins/Regional Groundwater Flow Systems.2.10 Springs.2.11 Groundwater in the United States.Problems.References.Chapter 3 Groundwater Movement.3.1 Darcy's Law.3.2 Permeability.3.3 Determination of Hydraulic Conductivity.3.4 Anisotropic Aquifers.3.5 Groundwater Flow Rates.3.6 General Flow Equations.3.7 Unsaturated Flow.Problems.References.Chapter 4 Groundwater and Well' Hydraulics.4.1 Steady Unidirectional Flow.4.2 Steady Radial Flow to a Well.4.3 Well in a Uniform Flow.4.4 Unsteady Radial Flow in a Confined Aquifer.4.5 Unsteady Radial Flow in an Unconfined Aquifer.4.6 Unsteady Radial Flow in a Leaky Aquifer.4.7 Well Flow Near Aquifer Boundaries.4.8 Multiple Well Systems.4.9 Partially Penetrating Wells.4.10 Well Flow for Special Conditions.4.11 Slug Tests.4.12 Slug Tests for Confined Formations.4.13 Slug Tests for Unconfined Formations.Problems.References.Chapter 5 Artificial Recharge, Stormwater Infiltration, and Saltwater Intrusion Prevention.5.1 Artificial Recharge.5.2 Stormwater Infiltration Basin Mound Development.5.3 Saline Water Intrusion in Aquifers.Problems.References.Chapter 6 Groundwater Flow Modeling.6.1 Introduction.6.2 Three-Dimensional Groundwater Flow Model.6.3 MODFLOW-2005 Description.6.4 Case Study: Using MODFLOW: Lake Five-O, Florida.6.5 Example Applications and Input of MODFLOW.Problems.References.Chapter 7 Hydrologic Processes.7.1 Introduction to Surface Water Hydrology.7.2 Precipitation (Rainfall).7.3 Evaporation.7.4 Infiltration.Problems.References.Chapter 8 Surface Runoff.8.1 Drainage Basins and Storm Hydrographs.8.2 Hydrologic Losses, Rainfall Excess, and Hydrograph Components.8.3 Rainfall-Runoff Analysis Using Unit Hydrograph Approach.8.4 Synthetic Unit Hydrographs.8.5 S-Hydrographs.8.6 NRCS (SCS) Rainfall-Runoff Relation.8.7 Curve Number Estimation and Abstractions.8.8 NRCS (SCS) Unit Hydrograph Procedure.8.9 Kinematic Wave Overland Flow Runoff Model.8.10 Computer Models for Rainfall-Runoff Analysis.Problems.References.Chapter 9 Reservoir and Stream Flow Routing.9.1 Routing.9.2 Hydrologic Reservoir Routing.9.3 Hydrologic River Routing.9.4 Hydraulic (Distributed) Routing.9.5 Kinematic Wave Model for Channels.9.6 Muskingum-Cunge Model.9.7 Implicit Dynamic Wave Model.9.8 Distributed Routing in U.S. Army Corps of Engineers HEC-RAS.Problems.References.Chapter 10 Probability, Risk, and Uncertainty Analysis for Hydrologic and Hydraulic Design.10.1 Probability Concepts.10.2 Commonly Used Probability Distributions.10.3 Hydrologic Design for Water Excess Management.10.4 Hydrologic Frequency Analysis.10.5 U.S. Water Resources Council Guidelines for Flood Flow Frequency Analysis.10.6 Analysis of Uncertainties.10.7 Risk Analysis: Composite Hydrologic and Hydraulic Risk.10.8 Computer Models for Flood-Flow Frequency Analysis.Problems.References.Chapter 11 Hydrologic Design and Floodplain Analysis.11.1 Hydrologic Design for Stormwater Management: Storm Sewers Design.11.2 Hydrologic Design of Stormwater Detention.11.3 Floodplain Analysis.11.4 Flood-Control Alternatives.11.5 Urban Flood Management: A Matter of Water Resources Sustainability.11.6 Water Supply for Crop Water Requirements: Evapotranspiration Calculations.11.7 Hydrologic Design for Water Supply.Problems.References.Chapter 12 Hydrologic Measurement.12.1 Atmosphere-Land Interface.12.2 Discharge Measurement.12.3 Streamflow Measurement.12.4 Groundwater Measurement.12.5 Automated Data Acquisition and Transmission Systems.12.6 Hydrologic Monitoring Systems.Problems.References.Chapter 13 Hydrology of Specific Climates.13.1 Hydrology of Arid and Semiarid Climates.13.2 Hydrology of Cold Climates.13.3 Hydrology of Humid Tropical Climates.13.4 Introduction to Watershed Hydrology Models.References.Appendix A Control Volume Approach for Hydrosystems.Continuity.Energy.Momentum.Appendix B NWS Precipitation Frequency Documents.Appendix C U.S. Army Corps of Engineers HEC-HMS.Watershed and Meteorological Description.Example Application.References.Appendix D U.S. Army Corps of Engineers HEC-RAS.HEC-RAS Model Features.Cross-Sections.Cross-Section Description for Conveyance Calculation.Cross-Section Interpolation.Cross-Sections at Junctions.Bridge Description.Encroachment Methods Floodplain Analysis.Reference.Index.
Includes bibliographical references and index.
Keywords: Hydrology